Age as an impediment to marriage under Polish law - STOJANOWSKA, WANDA (Prawo Kanoniczne, 2012)
In the essay there is an extensive study of Art. 10 of the Polish Family and Guardianship Code regulating the age enabling to marry – 18 years of age and conditions (premises) of issuing by the court a permission to enter into marriage granted to a woman who is at least 16 years old. The said scope of problems has been embraced in three points. The first point concentrates on the evolution of provisions of law concerning the lower limit of age enabling to enter into marriage, the second describes the premises of issuing by the Court a permission to enter into marriage regardless of an impediment to marriage, regulated by the above-mentioned Art. 10 and its practical use. The third point contains a summary comprising critical comments on the use of Art. 10 of the Polish Family and Guardianship Code by the court as well as conclusions de lege ferenda in order to improve the situation. One of the propositions was to make an amendment to the said Code by inserting new clauses regulating the way of preparing the betrothed (regardless of their age) for marriage as it is assumed by the Canon law.